Implementation of EU Environmental Policy in Ukraine: Directions and Perspectives - Golovko, Liudmyla; Kutsevych, Maksym; Serediuk, Viktoriia; Bogdan , Olga (European Journal of Sustainable Development, 2020)
The purpose of our article is to investigate the process of approximation of Ukrainian environmental legislation to EU law. The range of issues that Ukraine has reformed in the field of environment has been investigated. The state of compliance of Ukrainian environmental legislation with the commitments under the EU-Ukraine Association Agreement was revealed. The problems of further effective application in practice of the adopted regulatory legal acts, strategies and action plans were disclosed. Particular attention was paid to water legislation and legislation in the field of waste management. The current state of the sphere of solid waste management in Ukraine was revealed. The state of adaptation of Ukrainian water legislation to the requirements of the European Union law has been investigated. Ways to improve Ukraine's environmental policy on waste and water policy based on European experience were substantiated. The methods of comparative law, statistical, analytical and logical analysis were used. Keywords: EU Environmental policy, environmental law, EU water policy, EU waste policy, Ukrainian environmental legislation